Does one hydrogen atom matter? Crystal structures and spectroscopic studies of five-coordinate manganese porphyrin complexes. (March 2023) - Liang, Xu; Zhao, Jianping; Ren, Wanjie; Yuan, Yiwen; Guo, Wenping; Li, Jianfeng
Abstract: Metalloporphyrins and imidazole(ate) have long been employed to mimic metalloenzymes such as five-coordinate heme complexes. In this work, several five-coordinate manganese(II) porphyrin complexes utilizing sterically hindered 2-methylimidazole (2-MeHIm) or 2-methylimidazolate (2-MeIm‾) as axial ligand are isolated and characterized by single-crystal X-ray, UV–vis, DFT and electronic paramagnetic resonance (EPR) spectroscopies to explore their geometric and electronic structures. Both UV–vis and crystal structural investigations revealed noteworthy differences between the two species (e.g. the unusual Soret band split of 2-MeIm‾ derivatives) which are consistent with the stronger ligand nature of 2-methylimidazolate. Low temperature (4 K) EPR measurements have been carried out for all the products in both solid and solution states which gave characteristic signals of a high-spin (S = 5/2) d 5 system with g⊥ ≈ 5.9 and g// ≈ 2.0. Notably, the positive correlation between λ (E/D) and the numbers of hyperfine splittings are confirmed by double measurements e.g. [Mn(TPP)(2-MeHIm)] exhibits two more hyperfine splittings than [Mn(TMP)(2-MeIm‾)]‾ with a larger λ (0.018 vs. 0.002). Highlights: Several models for the common structural motif of high-spin five-coordinate heme species are isolated and studied. The models are fully characterized to explore their geometric and electronic structures. EPR studies verified the positive correlations between λ and the numbers of hyperfine lines.